Selected writings on visual arts and culture : detour to the imaginary - Hall, Stuart, 1932-2014 (Hall, Stuart, 1932-2014. Works. 2016., 2024)
"Selected Writings on Visual Arts and Culture brings together a variety of Stuart Hall's texts on visual art and culture, including essays, lectures, reviews, catalogue texts, and conversations. Hall wrote extensively on art, film and photography in the last decades of his career and chaired the Boards of two important Black British art organizations, Autograph and Iniva. The collection collects his thinking on images, film, photography, archives and museums in tandem with considerations of representation, Black identity, creolization, and African imaginaries. The volume provides insight into what Hall described as the "radically different" intellectual and aesthetic space of the visual imaginary"--